Transforming probation services in Magistrates’ courts - Robinson, Gwen (Probation journal, 2018)
This article presents findings from an exploratory study of court work in two English Magistrates’ courts which was conducted in 2017. The study involved two principal research methods: observation of the daily activities of court team members and semi-structured interviews with 21 members of the two teams, which took place towards the end of the research. The aim of this article is to provide an insight into contemporary probation work in Magistrates’ courts, in the wake of two major reform programmes: Transforming Rehabilitation and Transforming Justice. The findings of this study raise questions about the contemporary relevance of the ‘narrative of decline’ that has featured in previous research and commentary on court work, and further suggests that - whilst it is early days - the creation of specialist court teams has not inevitably led to the ‘incorporation’ of probation workers into the dominant court culture.